The physiological effect of pre-soaking with tryptophan on sugar beet (Beta vulgaris L.) productivity under different levels of salinity stresses - Hozayn, M. (2021)
The results revealed that the pre-soaking in tryptophan treatments (2.5 mM) were the most effective treatments under different salinity levels and caused significant increases in all tested parameters of this study. Moreover, increasing salinity levels decreased significantly the root purity parameters and increased impurity parameters of sugar beet. The DS-9004 cultivar gave the highest values of all studied parameters compared with the LP-15 cultivar under different salinity levels with tryptophan (2.5 mM). Chlorophyll a content and chlorophyll a/b ratio, as well as carotenoids content, were highest in DS-9004 cultivar, while chlorophyll b content was highest in LP-15 cultivar at 75 days.